Pembentukan Akhlak Karimah melalui Pengajaran Sastra Indonesia dengan Pendekatan Kurikulum Berbasis Kompetensi: Fostering Noble Character through the Teaching of Indonesian Literature Using a Competency-Based Curriculum Approach - Abd. Rahman Ds (Fenomena, 2007)
The prevalence of immoral behavior, violence, drug abuse, and promiscuity among Indonesian students is a critical issue that signals the failure of value education in schools. National education aims to develop students with noble character, yet the implementation of literature teaching as a vehicle for moral formation faces serious obstacles. This study aims to describe strategies for Indonesian Literature teaching in shaping akhlak karimah and to identify implementation constraints at Madrasah Aliyah Baitul Arqom Balung-Jember in the 2006/2007 academic year. Using a qualitative approach, data were collected through observation, in-depth interviews, and document analysis of syllabi, teaching materials, and evaluation systems. The main findings indicate that teachers had not independently developed syllabi, evaluation materials focused excessively on cognitive rather than affective and psychomotor aspects, and learning tended to be verbalistic-theoretical rather than appreciative. The study concludes that shaping akhlak karimah through Indonesian Literature teaching proved less strategic and less effective. It is recommended that teachers develop flexible syllabi, appreciative teaching materials, and holistic evaluations, and that schools provide complete literary works rather than synopses. Maraknya perilaku amoral, kekerasan, penyalahgunaan narkoba, dan pergaulan bebas di kalangan pelajar Indonesia menjadi isu krusial yang mengindikasikan kegagalan pendidikan nilai di sekolah. Pendidikan nasional bertujuan membentuk peserta didik berakhlak mulia, namun implementasi pengajaran sastra sebagai wahana pembinaan moral masih menghadapi kendala serius. Penelitian ini bertujuan mendeskripsikan strategi pembelajaran Sastra Indonesia dalam pembentukan akhlak karimah serta mengidentifikasi kendala implementasinya di Madrasah Aliyah Baitul Arqom Balung-Jember Tahun Pelajaran 2006/2007. Dengan pendekatan kualitatif, data dikumpulkan melalui observasi, wawancara mendalam, dan analisis dokumen silabus, bahan ajar, serta sistem evaluasi. Temuan utama menunjukkan bahwa guru belum menyusun silabus secara mandiri, materi evaluasi terlalu mengacu pada aspek kognitif dan bukan afektif serta psikomotorik, serta pembelajaran cenderung bersifat verbalistis-teoritis dan bukan apresiatif. Penelitian menyimpulkan bahwa pembentukan akhlak karimah melalui pengajaran Sastra Indonesia menjadi kurang strategis dan kurang efektif. Direkomendasikan agar guru menyusun silabus yang fleksibel, mengembangkan bahan ajar yang apresiatif, mengevaluasi secara holistik, serta sekolah menyediakan koleksi karya sastra utuh dan bukan sinopsis.